2004
DOI: 10.1111/j.1752-0606.2004.tb01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Student‐faculty Perceptions of Multicultural Training in Accredited Marrige and Family Therapy Programs in Relation to Students'self‐reported Competence

Abstract: Although the marriage and family therapy field's recent attention to multicultural issues is laudable, there appears to be little clarity on what constitutes an effective multicultural training program and the impact of the effects of such training on trainee multicultural competence. The field continues to be challenged at different levels-training, practice, research, the setting of the standards and the work of the Commission on Accreditation for Marriage and Family Therapy Education, and the goals and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…For example, Inman, Meza, Brown, and Hargrove (2004) provide several recommendations including increasing minority representation among faculty and students, and conducting more research on minority groups. Training programs in marriage and family therapy need to show commitment to diversity issues on many levels as a way to demonstrate the importance of these issues to the field.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Inman, Meza, Brown, and Hargrove (2004) provide several recommendations including increasing minority representation among faculty and students, and conducting more research on minority groups. Training programs in marriage and family therapy need to show commitment to diversity issues on many levels as a way to demonstrate the importance of these issues to the field.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, though many studies support the self-reported differences in students before and after multicultural courses are taken, the consensus is that the amount, quality, and diversity of information being utilized are insufficient (Inman, Meza, Brown, & Hargrove, 2004). Some of these limitations may be the result of the choices universities make on how to implement multicultural information in the curriculum and ultimately what actually happens as a result of these decisions.…”
Section: A Training Modelsmentioning
confidence: 82%
“…Specifically, a diversity-deprived environment (i.e., desegregation vs integration) engenders the cultivation or activation of internalized racism many students of color may have faced for a lifetime. Inman, Meza, Brown, and Hargrove (2004) observed that "faculty of color are important in serving as mentors and role models, as well as reflecting the experiences and cultures of students of color" (p. 384). Without the presence of other individuals of color, power differentials, cyclical systemic oppression, and disparities in the representative body of decision-makers is only perpetuated.…”
Section: Exemplary Programsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is not enough simply to have team members of different cultures/races informing and guiding practice. Deliberate engagement with the range of problems manifested through experience of diversity and injustice need attention (Inman, Meza, Brown & Hargrove, 2004;Guanipa 2003). Students' cultural contexts, their prejudices, biases and ethnicity added to a myriad of emotions and thoughts about contentious decisions taken within the therapeutic interventions.…”
Section: Recommendationsmentioning
confidence: 99%